2019
DOI: 10.1186/s12888-019-2197-1
|View full text |Cite
|
Sign up to set email alerts
|

Subjective experiences of neurocognitive functioning in young people with major depression

Abstract: Background: Research suggests that young people with major depressive disorder (MDD) experience neurocognitive deficits and that these are associated with poorer functional and clinical outcomes. However, we are yet to understand how young people experience such difficulties. The aim of the current study was to explore the subjective experiences of neurocognitive functioning among young people with MDD. Methods: Semi-structured qualitative interviews were conducted with 11 young people (aged 17-24 years) atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…11,35,36 Alternatively, cognitive failures in daily life may increase one's negative affect. 23 Research has shown that subjective cognitive impairment in mood disorders is associated with poorer socio-occupational functioning, 37,38 which may in turn have an impact on mood. A vicious cycle may ensue where cognitive difficulties and affective symptoms feed into one another.…”
Section: Comparison With Findings From Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…11,35,36 Alternatively, cognitive failures in daily life may increase one's negative affect. 23 Research has shown that subjective cognitive impairment in mood disorders is associated with poorer socio-occupational functioning, 37,38 which may in turn have an impact on mood. A vicious cycle may ensue where cognitive difficulties and affective symptoms feed into one another.…”
Section: Comparison With Findings From Other Studiesmentioning
confidence: 99%
“…A vicious cycle may ensue where cognitive difficulties and affective symptoms feed into one another. 23,36 When subjective cognitive impairment is perceived to have a negative impact on important aspects of daily life, the influence on the development or exacerbation of depression or anxiety symptoms may be greater. It is also possible that depleted cognitive resources are a consequence of poor sleep and mental fatigue, which are common in anxiety and depression.…”
Section: Comparison With Findings From Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Tickell et al [21] found that impairments in different neurocognitive domains were related to anxiety and stress, among others. In addition, a recent study revealed the association between neurocognitive functioning and depressive symptoms [22].…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive domains such as sustained attention or memory were related to anxiety and stress, among others. In another relevant study with young people between 17 and 24 years old, Morey-Nase et al [22] found that major depression was related to subjective experiences of neurocognitive functioning.…”
Section: Introductionmentioning
confidence: 98%